Cross talk between the bombesin neuropeptide receptor and Sonic hedgehog pathways in small cell lung carcinoma - Castellone, Maria Domenica (Oncogene, 2014)
Small cell lung carcinoma (SCLC) often features the up-regulation of the Sonic Hedgehog (Shh) pathway leading to activation of Gli transcription factors. SCLC cells secrete bombesin (BBS)-like neuropeptides (BLPs) that act as autocrine growth factors. Here, we show that SCLC tumour samples feature co-expression of Shh and BBS-cognate receptor (Gastrin-Releasing Peptide Receptor: GRPR). We also demonstrate that BBS activates Gli in SCLC cells, which is crucial for BBS-mediated SCLC proliferation because cyclopamine, an inhibitor of the Shh pathway, hampered the BBS-mediated effects. BBS binding to GRPR stimulated Gli through its downstream Gα(q) and Gα(12/13) GTPases, and consistently, other Gα(q) and Gα(13) coupled receptors (such as muscarinic receptor, m1, and thrombin receptor, PAR-1) and constitutively active Gα(q)QL and Gα(12/13)QL mutants stimulated Gli. By using cells null for Gα(q) and Gα(12/13), we demonstrate that these G proteins are strictly necessary for Gli activation by BBS. Moreover, by using constitutively active Rho small G-protein (Rho QL) as well as its inhibitor, C3 toxin, we show that Rho mediates GPCR-, Gα(q)- and Gα(12/13-)dependent Gli stimulation. At the molecular level, BBS caused a significant increase in Shh gene transcription and protein secretion that was dependent on BBS-induced GPCR/Gα(q-)(12/13)/Rho mediated activation of NFκB, which can stimulate a NFκB response element in the Shh gene promoter. Our data identify a novel molecular network acting in SCLC linking autocrine BBS and Shh circuitries, and suggest Shh inhibitors as novel therapeutic strategies against this aggressive cancer type.